A case of fulminant varicella infection with purpura fulminans, hepatitis, and rhabdomyolysis - A S Karadag; S G Bilgili; O Calka; I Çeçen; S Akbayram (Wolters Kluwer Medknow Publications, 2012)
Varicella zoster virus causes varicella which is a common disease. Generally it is self-limiting, and treatment is often unnecessary, but severe or life-threatening complications are rarely seen. We report a case of fulminant varicella complicating with purpura fulminans, hepatitis, and probable rhabdomyolysis in a previously healthy child.